High-Throughput Identification of Antibacterials Against Pseudomonas aeruginosa - Li, Shijia; She, Pengfei; Zhou, Linying; Zeng, Xianghai; Xu, Lanlan; Liu, Yaqian; Chen, Lihua; Wu, Yong (Frontiers in Microbiology, 2020)
Antibiotic resistance is a growing public health concern, though the constant development of new antibiotics. The combination of high-throughput screening and drug repurposing is an effective way to develop new therapeutic uses of drugs. In this study, we screened a drug library consisting of 1,573 drugs already approved by the Food and Drug Administration and 903 drugs from the natural product library, to identify antimicrobials against Pseudomonas aeruginosa. A high-throughput screening assay based on microtiter plate was used to screen 39 drugs that inhibit the planktonic or biofilm formation of P. aeruginosa while most of them are antibiotics. The antimicrobial activities of these drugs were evaluated by phenotypic analysis. Further studies showed the combined therapy of tetracycline antibiotics demeclocycline hydrochloride (DMCT) and the novel antimicrobial peptide SAAP-148 has an effective synergistic antibacterial effect on P. aeruginosa PAO1 and P. aeruginosa ATCC27853. Moreover, the time-kill curve assay and murine model of cutaneous abscesses further confirmed the synergistic effect. In addition, the combination of DMCT and SAAP-148 has the potential to combat clinically isolated multidrug-resistant (MDR) P. aeruginosa strains. Our results clearly indicate that DMCT and SAAP-148 combined therapy could be an effective method to combat MDR P. aeruginosa-related infections.